MANIFESTATIONS OF NSAID-GASTRODUODENOPATHY IN PATIENTS WITH KNEE OSTEOARTHRITIS. (LITERATURE REVIEW) (World Bulletin of Public Health, 2023)
The article presents the effect of non-steroidal anti-inflammatory drugs (NSAIDs) on the gastrointestinal tract (GIT) and the pathogenesis of gastroduodenopathy in patients with knee osteoarthritis (KOA)